The nematode Caenorhabditis elegans and diverse potential invertebrate vectors predominantly interact opportunistically - Petersen, Carola; Krahn, Alexandra; Leippe, Matthias (Frontiers in Ecology and Evolution, 2023)
Some small animals migrate with the help of other, more mobile animals (phoresy) to leave short-lived and resource-poor habitats. The nematode Caenorhabditis elegans lives in ephemeral habitats such as compost, but has also been found associated with various potential invertebrate vectors. Little research has been done to determine if C. elegans is directly attracted to these invertebrates. To determine whether C. elegans is attracted to compounds and volatile odorants of invertebrates, we conducted chemotaxis experiments with the isopods Porcellio scaber, Oniscus asellus, and Armadillidium sp. and with Lithobius sp. myriapods, Drosophila melanogaster fruit flies, and Arion sp. slugs as representatives of natural vectors. Because phoresy is an important escape strategy in nature, especially for dauer larvae of C. elegans, we examined the attraction of the natural C. elegans isolate MY2079 in addition to the laboratory-adapted strain N2 at the dauer and L4 stage. We found that DMSO washing solution of Lithobius sp. and the odor of live D. melanogaster attracted C. elegans N2 L4 larvae. Surprisingly, the natural isolate MY2079 was not attracted to any invertebrate during either the dauer or L4 life stages and both C. elegans strains were repelled by various compounds from O. asellus, P. scaber, Armadillidium sp., Lithobius sp., and Arion sp. feces. We hypothesize that this is due to defense chemicals released by the invertebrates. Although compounds from Lithobius sp. and D. melanogaster odorants were mildly attractive, the lack of attraction to most invertebrates suggests a predominantly opportunistic association between C. elegans and invertebrate vectors.